2016
DOI: 10.1310/hpj5106-461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clevidipine versus Sodium Nitroprusside for the Treatment of Postoperative Hypertension in Cardiac Surgery Patients

Abstract: Objective:To evaluate the efficacy and safety of clevidipine (CLV) versus sodium nitroprusside (SNP) for the treatment of hypertension (HTN) in postoperative cardiac surgery patients at a community hospital. Methods: This single-center, retrospective, cohort study included cardiac surgery patients treated with CLV or SNP for postoperative systolic blood pressure (SBP) control. The primary efficacy outcome was defined as the mean number of times the SBP rose above 140 mm Hg. Secondary outcomes included a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Analysis of 40 patients, showed that the safety and use of clevidipine or sodium nitroprusside as alternative as-needed antihypertensive medications were essentially the same. 10 When comparing sodium nitroprusside and nicardipine (CCB) in a recent United States systematic review and meta-analysis of 5 studies of postsurgical hypertensive management (N ¼ 571 patients), the authors established that there was no difference in BP-lowering effects between nitroprusside and nicardipine. 11 A retrospective cohort study involving 210 patients in the emergency department with ischemic or hemorrhagic strokes established that clevidipine (50 [SD, 83] minutes and nicardipine (74 [SD, 103] minutes) both achieved the systolic BP goal (P ¼ .101).…”
Section: The Mnemonicmentioning
confidence: 99%
“…Analysis of 40 patients, showed that the safety and use of clevidipine or sodium nitroprusside as alternative as-needed antihypertensive medications were essentially the same. 10 When comparing sodium nitroprusside and nicardipine (CCB) in a recent United States systematic review and meta-analysis of 5 studies of postsurgical hypertensive management (N ¼ 571 patients), the authors established that there was no difference in BP-lowering effects between nitroprusside and nicardipine. 11 A retrospective cohort study involving 210 patients in the emergency department with ischemic or hemorrhagic strokes established that clevidipine (50 [SD, 83] minutes and nicardipine (74 [SD, 103] minutes) both achieved the systolic BP goal (P ¼ .101).…”
Section: The Mnemonicmentioning
confidence: 99%
“…Some kinds of the samples were also tested in clinical laboratories, e.g. [21]. Other indicators were also applied for this purpose, see [22].…”
Section: Calculation Proceduresmentioning
confidence: 99%